Optimizing Ventilation Strategies for Thermal Comfort in Mediterranean Schools: A Dynamic Modeling Approach - Paolo Maria Congedo; Andrea Palmieri; Cristina Baglivo (Energies)
Schools, key symbols of progress and innovation, require particular attention regarding energy efficiency, which is considered a strategic priority in sustainable development policies. Improving energy efficiency in schools reduces costs and environmental impact while educating students and the community about sustainability. Ensuring good air quality and thermal comfort is also crucial for student well-being and performance, resulting in improved productivity, health, and concentration. This study shows that proper ventilation in schools can maintain thermal comfort by exploiting the heat loads generated by the environment and equipment. Yearly and hourly analyses were conducted in terms of internal operative temperature on a simplified school prototype located in a Mediterranean city following the UNI EN ISO 52016 standard. Thermal comfort was evaluated in accordance with the UNI EN 16798-1 standard and tested for different air exchange rates. The results showed that the heating system would typically operate for about 1000 h per year, excluding holiday periods when teaching activities are suspended. With the implementation of a suitable ventilation system, however, the need for a heating system could be removed.